Study of the Influence of the Voltage Regulator Integrated Circuit Topology on its Radiation Hardness - Е. A. Кulchenkov; A. A. Demidov; S. B. Rybalka (Приборы и методы измерений, 2025)
Method of recording responses to radiation exposure is considered using the X-ray complex RIK-0401 and it is shown that for linear voltage regulators integrated circuits it allows diagnosing presence of changes in their topology. Four types of integrated circuits (ICs) of IS-LS1-1.8V type have been studied. They are equivalent in their main electrical parameters, but have differences in the output key design (vertical transistors with different base wiring), current mirrors and differential stages. ICs have modified design of the output key base: 1) vertical p-n-p-structures (Type 1); 2) mixed (lateral+vertical) p-n-p-structures (Type 2); 3) design as in the foreign analogue and vertical p-n-p-structures (Type 3); 4) design as in the foreign analogue and mixed (lateral+vertical) p-n-p-structures (Type 4). It has been found that the highest radiation hardness to the total ionizing dose effects is demonstrated by samples of Type 1 and Type 2. RADON-23 laser complex (with a maximum energy density of 200 mJ/cm2) has been used for examination of voltage regulator samples to impulse ionizing radiation hardness. The thyristor effect has not been fixed in all studied samples of Type 1–4. Results of the research allow developing methods for increasing the radiation hardness of the IS-LS1-1.8V by varying the topology of microcircuits and choosing the most advantageous option for manufacturing the output key.